Topical Application of Mesenchymal Stromal Cells Ameliorated Liver Parenchyma Damage After Ischemia-Reperfusion Injury in an Animal Model - Lam, Ping Kuen (Transplant Direct, 2017)
BACKGROUND: Ischemia-reperfusion injury (IRI) is commonly encountered after liver surgery. This study evaluated the hepatoprotective effects of topically applied adipose-derived mesenchymal stromal cells (ADMSCs) on hepatic IRI in a rat model. METHODS: ADMSCs from transgenic green fluorescent protein Sprague-Dawley rats were topically applied to the liver surface of Sprague-Dawley rats after hepatic IRI and fixed in position by fibrin glue (group A, n = 24). An equivalent amount of ADMSCs were administered through the portal (group B, n = 24) or tail vein (group C, n = 24). In the control group (group D, n = 20), no treatment was given to the IRI liver. RESULTS: All the rats in group A and group D survived. Within 2 days after hepatic IRI, only 50% of rats survived in group B, and ADMSCs were detected in thromboemboli within large vessels. 62.5% of the rats died in group C because most of the ADMSCs were trapped in the lungs. ADMSCs migrated across the liver capsule and homed to the injured liver parenchyma 3 days after topical application in group A. The homed ADMSCs expressed hepatocyte nuclear factor-4α and hepatocyte nuclear factor-1. Compared with group D, the rate of hepatic regeneration in group A was enhanced with less inflammation, smaller necrotic areas, and improved liver function. Proinflammatory cytokines IL-6, IL-21, and CD70 were significantly downregulated in group A by 6.3-, 2.7-, and 12.7-fold, respectively (P < 0.05). The neurogenic locus NOTCH homolog protein pathway was activated in the topical ADMSCs. CONCLUSIONS: Topically applied adipose-derived mesenchymal stromal cells demonstrated hepatoprotective effects on hepatic IRI in an animal model.